Catfish Culvation (Pangasius hypothalmus) Business Income with Production Risks in Banjar District, South Kalimantan Province - Santoso, Aprilia Anggi; Syaukat, Yusman; Fariyanti, Anna (Jurnal AGRISEP, 2024)
Catfish (Pangsianodon hypopthalmus) is a type of economical fish that is quite popular with the public. Production of Catfish cultivation in Banjar Regency has decreased, due to flooding as a factor influencing production risk. The existence of production risks in the Catfish cultivation business also greatly influences the income of Catfish cultivators. The aim of this research is to analyze the income of Catfish cultivation businesses in the presence of production risks. This research was conducted in Martapura District and West Martapura District, Banjar Regency. The number of Catfish cultivators in the sample was 41 respondents. The type of data used in This research was used panel data. Business income is analyzed using the R/C ratio and the value of expected income when production risks occur is measured using expected return. The results of the analysis show that the Catfish cultivation business has an R/C ratio > 1 and the expected return value is positive, namely IDR 5,431,767.27. The probability that there is a production risk, namely flooding, shows that the Catfish cultivation business in Banjar Regency is efficient and therefore feasible to run.